Studi Kelayakan Bisnis Pada Brand Baju Muslim Sabhira_co - Agus Sutardi; Anggini Hardiyanti; Intan Yulia Azzahra; Rosa Amelia; Hilman Al Hafizh; Azamni Dhohirudin (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Fashion Sabhira is a business that grew from a reseller business to a distributor with a unique history. Sabhira was established on August 28, 2016 first operating as a reseller and distributor who takes goods from others. When the shop in Andir became very popular, Sabhira decided to open her own shop on Jln. Bengawan, Bandung. started to build its own brand with the name